Políticas crediticias y de cobranza en la empresa "Edmar & Torres Y Cía.", año 2016: un estudio retrospectivo. - Alejandro Villalta, Patricia Elizabeth (2018)
The research work was conducted in the city of Machala, province of El Oro, in the company called Edmar & towers and Cia., which is dedicated to the marketing of balanced Nicovita shrimp, takes 4 years in the market, being one of the great companies in this commercial activity, it has approximately more than 150 customers, those who have a direct credit, most of them have signed contracts or you promissory notes as guarantee that since its inception began to have trade relations with the company, most because of this has been given inconsistencies by debts in certain clients since the company has granted credit without any backing and this did raise the non-performing loans and has diminished its liquidity, for this reason we will proceed and will focus it for the case on credit policies and collection analysis. With the passing of time the competitiveness in the commercial area has been very strong, so that companies must have strategies under the sleeve that help and facilitate business relationships with the customer, direct loans are the bread of the day in the commercial market . Trade credit is a few elements more old and "classical" in the negotiation of a provider versus debtor (singing caves, Palacìn Sanchèz, & Di Prieto, 2016). Competition on the credit are direct, financial loans granted by financial institutions, "consumer credit" portfolio will benefit the financial entity (Diaz & Valle Guerra, 2017), give credits to customers to use these to trading houses and have a warranty on your purchases will help greatly in reducing the nonperforming loans, although in the majority of cases customers do their commercial transactions with postdated checks and eh there is possible risk in the accounts bad, because in present times the nonperforming loans has been more for returned checks, insufficient funds, cancelled accounts etc., the Council would be that the company maintains an excellent relationship with the financial institution, which is the same as time make an analysis of clients by reviewing their financial statements. Currently, the company Edmar Torres & Cia., has defined legally their policies of credit and collections, the same that help ensure proper management in the recovery of its portfolio and lead to improve its liquidity and reduce late payments in the trading house. Based on this deficiency, is the research and analysis of the case, taking tools such as the use of scientific, quantitative and qualitative methodologies, use of interviews and observation guides, also use conceptualizations, definitions that help to have clearer perspective of this case study, which will help us to the development of this qualification work starting from the approach of the problem until the objectives, all gathering information we provide a contribution to proceed to formulate research questions, directed and framed to the proposed objectives, immediately encasillaremos us to the analysis of them and we will finish with the sample of conclusions and will give our recommendations, this way will try to contribute in this area of credit and collections.